(untitled) (Fiep Bulletin - online, 2014)
This article is originated from research with educators from schools, early childhood education and other training courses in which operate. From corporeity emphasis, the movement, the play, to toys, the emotions, the body finally speaking. It is a search for quality stamp which was to vivacious, groups of discusses, comments the halls of classes, talk to educators, films, photographs. Our purpose was to encourage educators to the thematic weight of corporeity play in the halls of lessons from their mem6rias from their memories. The realization that body movement as language permit effective relations and the construction of new knowledge, stimulate the mind and allow the educators a reflection on the corporeity in schools. The vivacious allowed relax in gestures, in speaking of the body. The debates were important to establish new relations and the world. Breaking taboos, leaving the routine, rewrite stories, review concepts, Take flights, and change the daily life of rooms for classes. Building environments of meetings where the humility, the kindness, tolerance, security, the decisions and the verbal parsimony were in constant meetings with the joy of living in full.